Finding moving-band statistical arbitrages via convex–concave optimization - Johansson, Kasper; Schmelzer, Thomas; Boyd, Stephen (Optimization and engineering, 2025)
We propose a new method for finding statistical arbitrages that can contain more assets than just the traditional pair. We formulate the problem as seeking a portfolio with the highest volatility, subject to its price remaining in a band and a leverage limit. This optimization problem is not convex, but can be approximately solved using the convex–concave procedure, a specific sequential convex programming method. We show how the method generalizes to finding moving-band statistical arbitrages, where the price band midpoint varies over time.